(untitled) (LEARNing Landscapes, 2009)
The majority of English Language Arts curricula in North America, if not worldwide, draw on traditional literary texts as their core content. By contrast, the confluence of image and written word on contemporary texts—including the literary—and the impact this evolution has on our comprehension of the changing face of literacy is one of the most compelling issues in contemporary pedagogy. It seems clear that the rise of the new media and its range of textual genres challenge prevailing views about what it means to be a reader and how reading is taught in our schools. Since word and image demand different reading paths and strategies, how can teachers begin to re-vision their pedagogical practices while taking an active role in addressing the literacy needs of their elementary and secondary students?